Pelatihan Membuat Lembar Kerja Peserta Didik (LKPD) Bagi Guru Sekolah Dasar - Kadeni, Kadeni; Santoso, Ekbal (EDUPEDIA Publisher, 2022)
In order to deal with technological advances and improve the quality of basic education human resources, teachers as the main executors of the educational process must be willing and able to improve their competence. One of the determinants of the quality of learning is that the teacher has learning tools that are in accordance with the characteristics of the school and students. One of the important learning tools is student worksheets (LKPD). The purpose of this training is to assist teachers in creating and preparing worksheets that are able to improve student achievement. The methods used are lectures, discussions and practicum. The results of this training were that all participants were able to make worksheets that match the criteria and are appropriate for students to use in learning. From these results it is hoped that the training participants will continue to improve their competence in order to produce more interactive worksheet products to achieve maximum learning outcomes.